Exploring The Impact Of Dialysis On Neurological Conditions: Insights From Biochemical Data In Chronic Kidney Disease - Thamer, Ahmed Kareem (PT. Antis International Publisher, 2024)
When an individual goes through dialysis in chronic kidney disease, the substances located in the bodies of patients undergo considerable fluctuations. Creatinine and urea are considered as kidney function indicators. In this regard, urea is an indicator of kidney change, and creatinine reflects the efficiency of glomerular filtration. The following data are markers that need to be kept on the observation under individuals on dialysis. The goal of the investigation is the biochemical parameters ratio pick up that can reflect the patients’ neurological state on dialysis. To ensure the transparency and reliability of the data sources, systematic review of scientific and methodological literature represented in the electronic databases VHL, Google scholar, SciELO, and recent publications from 2014-2023 has been carried out. Development of this subject has had given to the relationship of biochemical variables to CKD, creatinine, and urea. inclusion summary is provided. Research stakeholders included studies that were associated with patients’ biochemical variables and compared the denatured changes among bio-variable changes both before and after Dialysis. With the extracted data shown and analyzed how the dialysis treatment has impacted on patients with CKD regarding bio-variable changes. Results: the systematic review lead to a great change report in biochemical patients bio-variable among persistent kidney disease. Hemodialysis was a significant intervention since it influences metabolic values towards normalcy. Creatinine and urea were seen to be affected much since their levels of changes indicated abnormalities of kidney organs. Therefore data extracted remain valuable in that, it is required for any regular check in patients undergoing dialysis treatment. Conclusion: It is imperative that healthcare providers treating patients with CKD on dialysis be well versed with biochemical indicators such as creatinine and urea, and understand their importance in patient management. Appropriate and timely monitoring of these markers enables healthcare professionals to initiate prompt intervention and treatment adjustments to enhance patient care and quality of life. Based on these findings, the current systematic review studies demonstrate the significance of biochemical data in providing insights into the neurological state and management options for CKD patients under dialysis